Corrosion of Buried Pipelines by Stray Current in Electrified Railways: Mechanism, Influencing Factors, and Protection - Haiming Liang; Yuxi Wu; Bin Han; Nan Lin; Junqiang Wang; Zheng Zhang; Yanbao Guo (Applied Sciences)
Metal pipes are often interfered with by currents of irregular frequency and wavelength. This is called stray current interference. The corrosion of metal pipes caused by stray current interference is one of the many factors contributing to their deterioration. Pipeline corrosion and leakage caused by stray currents can significantly impact the safety, environment, and economy of the surrounding areas. Over the past few years, stray current interference has become one of the research hotspots in the petrochemical and natural gas transportation industries. This review article investigates accident cases caused by stray currents and compares the corrosion mechanisms of DC stray currents and AC stray currents, analyzes the influence of pipeline material, environment, voltage and current, stress, and other factors on corrosion, and puts forward corrosion protection measures, such as cathodic protection, coating technology, internal corrosion control, and means of detecting stray current corrosion. Finally, it provides an outlook on future research directions on corrosion protection against stray currents.